2022
DOI: 10.3390/ph15030322
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Seasonal Influenza Vaccination: Cross-Protection, Co-Administration, Combination Vaccines, and Hesitancy

Abstract: SARS-CoV-2 and influenza are the main respiratory viruses for which effective vaccines are currently available. Strategies in which COVID-19 and influenza vaccines are administered simultaneously or combined into a single preparation are advantageous and may increase vaccination uptake. Here, we comprehensively review the available evidence on COVID-19/influenza vaccine co-administration and combination vaccine candidates from the standpoints of safety, immunogenicity, efficacy, policy and public acceptance. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 72 publications
0
42
0
2
Order By: Relevance
“…Although some healthcare workers even opted for the coadministration, many others expressed concerns about the administration within a short period of time, therefore preferring to prioritize the SARS-CoV-2 vaccination and, thus, avoiding the flu one. The main reasons [49] seem to be the fear of the pandemic situation and especially in the uncertainty related to the consequences of a concurrent administration which may overload the immune system or may be more reactogenic, despite the availability of evidence-based recommendations demonstrating its safety and immunogenicity [50]. Moreover, another reason might be the spread of anti-vaccine movements, deriving from the COVID-19 vaccination campaign, even among HCWs, which might also affect the flu vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Although some healthcare workers even opted for the coadministration, many others expressed concerns about the administration within a short period of time, therefore preferring to prioritize the SARS-CoV-2 vaccination and, thus, avoiding the flu one. The main reasons [49] seem to be the fear of the pandemic situation and especially in the uncertainty related to the consequences of a concurrent administration which may overload the immune system or may be more reactogenic, despite the availability of evidence-based recommendations demonstrating its safety and immunogenicity [50]. Moreover, another reason might be the spread of anti-vaccine movements, deriving from the COVID-19 vaccination campaign, even among HCWs, which might also affect the flu vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while more than 60% of all respondents agreed with COVID-19 vaccine co-administration, hesitancy towards co-administration is greater than hesitancy towards the COVID-19 vaccine alone. While there is some evidence to support this finding [ 12 ], one study found that a combination influenza/COVID-19 vaccine had higher acceptance than a COVID-19 vaccine alone [ 39 ]. More work is required to understand whether and how acceptance of co-administration differs from acceptance of combination vaccines, and whether these options differentially impact uptake across populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, adult perceptions on ongoing booster doses (i.e., annual COVID-19 vaccination) are largely unknown, and evidence on additional vaccine dose acceptance among Canadian adults, particularly among populations who may be at greater risk for COVID-19 infection and/or severe illness, is required. To ensure that COVID-19 vaccination programs are both acceptable and sustainable, we need an understanding of perceptions on strategies used to promote vaccine uptake over the long term, including vaccination mandates and restrictions, vaccination locations, and COVID-19 vaccine co-administration with other vaccines [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that COVID-19 vaccination programs are both acceptable and sustainable, we need an understanding of perceptions on strategies used to promote vaccine uptake over the long term, including vaccination mandates and restrictions, vaccination locations, and COVID-19 vaccine co-administration with other vaccines. (12) The aim of this study was to determine Canadian adults' intention for receiving additional doses of COVID-19 vaccine (i.e., third or annual doses), and examine factors associated with acceptance. We further sought to understand influences on vaccination decision-making, and preferences around vaccine delivery location, and COVID-19 vaccine co-administration.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that COVID-19 vaccination programs are both acceptable and sustainable, we need an understanding of perceptions on strategies used to promote vaccine uptake over the long term, including vaccination mandates and restrictions, vaccination locations, and COVID-19 vaccine co-administration with other vaccines. (12)…”
Section: Introductionmentioning
confidence: 99%